2021
DOI: 10.3390/su13052496
|View full text |Cite
|
Sign up to set email alerts
|

Are Professionals Rationals? How Organizations and Households Make E-Car Investments

Abstract: This study attempts to identify the main drivers for e-car investments in households and organizations. We questioned 227 decision makers in households currently considering car purchases, and 101 decision makers in small businesses. The businesses were private care services, because their driving profiles widely fit the capabilities of modern e-cars. The main investment drivers were compared in an integrated action model involving elements of the theory of planned behavior and the norm-activation model, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Consumer preferences and purchase decisions are essential components for high market penetration of ZLEVs in the long run. Surveys have shown that the factors of electric vehicle adoption include moral and social motives (Kastner et al, 2021;Bobeth and Kastner, 2020), charging infrastructure concerns (Haustein and Jensen, 2018), and real life usage experience (Jensen et al, 2014), among others. However, preferences can change over time as shown by Keller et al (2021).…”
Section: Consumer Preferencesmentioning
confidence: 99%
“…Consumer preferences and purchase decisions are essential components for high market penetration of ZLEVs in the long run. Surveys have shown that the factors of electric vehicle adoption include moral and social motives (Kastner et al, 2021;Bobeth and Kastner, 2020), charging infrastructure concerns (Haustein and Jensen, 2018), and real life usage experience (Jensen et al, 2014), among others. However, preferences can change over time as shown by Keller et al (2021).…”
Section: Consumer Preferencesmentioning
confidence: 99%